Elementy biblioterapii w literaturze polskiej epok dawnych. Rekonesans historycznoliteracki - Wichowa, Maria (Acta Universitatis Lodziensis. Folia Librorum, 2013)
Despite the fact that bibliotherapy is a relatively new subject of academic study, its origins as a cultural phenomenon date back to the ancient times. In European culture one can find numerous metaphors related to the book: the world as a written book, the book of nature, the book of experience, the book of life. In fine arts the book has become a symbol of intellectual activity.Our culture abounds in evidence that the cult of the book was also present in Old Poland. Intellectuals and artists praised culturally significant written works, admired famous book collections and their owners, valued their social standing as the Polish men of letters as well as acknowledged the therapeutic effects of literature. One of the prominent authors, Jan Amos Komeński, perceived the book as the most powerful tool of education. Biernat of Lublin claimed that books were the best companions and interlocutors. Bibliotherapy as a means of education was also recommended by Mikołaj Rej. In his work Żywot człowieka poczciwego he analyzed the influence of books on the process of shaping human personality. According to Rej, bibliotherapy in order to be effective should be handled in moderation and under no compulsion. Wespazjan Kochowski was another author to write about taking delight in reading with regards to its healing effects. He underlined various benefits obtained through reading together with its therapeutic qualities. Kochowski claimed that reading makes it possible for many people to achieve selfrealization as well as prompts taking action on the political and social arena. Stanisław Herakliusz Lubomirski praised literature in his work Adverbia moralia. He treated it as an attribute of evolution, an object of glorification, and a cure for the human soul trying to discover its own way. The first Polish encyclopedist, the Reverend Benedykt Chmielowski, in Nowe Ateny worshipped literature as the sacred and precious heritage which should be protected as a means of transmission of the ancient culture tradition. He viewed his own writing as a useful service to Polish literary culture. Similarly, Ignacy Krasicki perceived the book as a source of wisdom, cult object, and a means of spiritual therapy. In Old Poland the book was the most important medium of communication conveying the values constituting a cure for the soul.